2014
DOI: 10.1590/0103-9016-2013-0338
|View full text |Cite
|
Sign up to set email alerts
|

Spectral indices for the detection of salinity effects in melon plants

Abstract: ). Spectral data of leaves were transformed into vegetation indices indicative of the physiological status of the plants. The results showed differences for N (p < 0.05), K and Na content (p < 0.01) due to salinity suggesting different degrees of salt stress on the plants. Specific leaf area increased with salinity levels (p < 0.001). The capabilities of VNIR radiometry to assess the influence of soil salinity on melon physiology using a non-destructive method were demonstrated. A normalized difference vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…() reported that increasing levels of soil salinity generally induced a decrease in leaf reflectance in the NIR spectral region. In contrast, Hernández, Melendez‐Pastor, Navarro‐Pedreño, and Gómez () reported that the NIR spectral region from melon plants increased with increasing salinity levels. The NIR value of salt‐sensitive plants decreased with increasing salinity levels, while it increased firstly and then decreased in the salt‐tolerant plants (Wang et al., ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…() reported that increasing levels of soil salinity generally induced a decrease in leaf reflectance in the NIR spectral region. In contrast, Hernández, Melendez‐Pastor, Navarro‐Pedreño, and Gómez () reported that the NIR spectral region from melon plants increased with increasing salinity levels. The NIR value of salt‐sensitive plants decreased with increasing salinity levels, while it increased firstly and then decreased in the salt‐tolerant plants (Wang et al., ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, several studies suggest the use of agro-morphological traits such as shoot and leaf parameters, chlorophyll content, salinity injury score, stem reserve utilization for grain filling, and formation and viability of reproductive organs as criteria for classification of crop genotypes for salinity tolerance (De Leon et al, 2015; El-Hendawy, ; El-Hendawy, Hu, Yakout et al, 2005;Hern andez, Melendez-Pastor, Navarro-Pedreño, & G omez, 2014;Hairmansis, Berger, Tester, & John Roy, 2014;Kaya, Tuna, Ashraf, & Altunlu, 2007;Montes, Technow, Dhillon, Mauch, & Melchinger, 2011). However, efficient evaluation of salt tolerance too often requires assessing genotypes based on multiple favourable traits at different growth stages (De Leon et al, 2015;El-Hendawy, Hu, Yakout et al, 2005;El-Hendawy, Hu, & Schmidhalter, 2007;Zeng et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in agreement with previous results demonstrating the effects of NaCl stress on SLA. Tedeschi et al (2011) and Hernández et al (2014) found an increase in SLA in melon grown under salt stress.…”
Section: Vegetative Characteristicsmentioning
confidence: 95%
“…This behavior of spectral reflectance is associated with a decrease in Chl content (low chlorophyll absorption in the VIS region) and plant biomass (multiple scattering of NIR region by different leaf tissues) because of salinity stress. Previous studies have reported that when the Chl content decreases, the spectral reflectance in the VIS region increases especially in the main absorption bands of chlorophyll (blue: 400-500 nm and red: 660-690 nm) of the VIS spectrum [13,[63][64][65]. In addition, decreased biomass accumulation and substantial changes in several leaf structures because of ion toxicity and imbalance of salinity stress leads to decreased spectral reflectance in the NIR region, because of a multiplicative effect on the wavebands in the NIR region [30,59,65].…”
Section: Performance Of Different Types Of Spectral Reflectance Indexmentioning
confidence: 99%